Prospective study on a novel treatment for leaking cystic bleb: Efficacy and safety of collagen crosslinking. (17th May 2019) - Cai, Yu; Choy, Bonnie N. K.; Zhu, Ming M.; Li, Bai B.; Chan, Jonathan C. H.; Ho, Wing L.; Lai, Jimmy S. M.
Abstract: Importance: Management of cystic bleb leak is difficult. It would be essential to look for a method to strengthen the original pathological conjunctiva and reverse bleb leak. Background: To evaluate the long‐term efficacy and safety of collagen crosslinking in patients with leaking cystic bleb. Design: Prospective interventional case series at a university‐based hospital. Participants: Twelve eyes in 12 subjects with late‐onset bleb leak from cystic bleb, without indications for prompt surgical interventions were included. Methods: The subjects underwent crosslinking with 0.1% riboflavin application to bleb surface, followed by ultraviolet irradiation for 30 minutes. The subjects were followed up at baseline and at 1 week, 1 month, 3 months, 6 months post‐treatment and then every 6 months afterwards. Main Outcome Measures: Interval from treatment to cessation of bleb leak, recurrence rate of bleb leak and side effects of treatment. Results: The mean follow‐up after crosslinking was 29.33 ± 12.45 months. Bleb leak subsided in 11 (92%) of 12 patients after a single session of crosslinking, after 1 to 8 weeks (median 3 weeks). Time to leak cessation was significantly correlated with the number of prior glaucoma interventions ( R = .71, P = .014). Bleb wall at 3 months was significantly thicker than at baseline (0.70 ± 0.67 vs 0.81 ± 0.62 mm, P = .008). None of the patients experienced any complications. Conclusions and Relevance: Crosslinking achieves resolution of cystic bleb leak which lasts for at least 12 months, without the need of subsequent surgical interventions. Crosslinking is a simple, non‐invasive treatment for bleb leak. It aims to restore the integrity of conjunctiva.